Palatal lateral approximant /ʎ/ as one of the main troublemakers in learning croatian as L2 - Dobrić, Arnalda (Array, 2013)
According to the Verbotonal theory, speakers of L1 choose the closest sound from their own phonological system instead of the correct sound when learning L2 in adult age and the errors are consistent regarding their common L1 as well as targeted L2. This phenomenon is referred to as the system of errors. Most of adult speakers of different L1 learning Croatian as L2 often have major problems pronuncing palatal lateral approximant /ʎ/ substituting it with several sounds. The palatal lateral approximant /ʎ/ was corrected in eight native speaker of South American varieties of Spanish. The tested subjects were recorded before and after ten sessions of speech correction. Acoustic analysis in Praat showed statistically significant higher F2 in /ʎ/ in second recording and as well as significant difference in duration. Application of this sort of work can be seen in foreign language acquisition but also in research of speech-hearing pathology. Keywords : Verbotonal theory, speech correction, system of errors, palatal lateral approximant / According to the Verbotonal theory, speakers of L1 choose the closest sound from their own phonological system instead of the correct sound when learning L2 in adult age and the errors are consistent regarding their common L1 as well as targeted L2. This phenomenon is referred to as the system of errors. Most of adult speakers of different L1 learning Croatian as L2 often have major problems pronuncing palatal lateral approximant /ʎ/ substituting it with several sounds. The palatal lateral approximant /ʎ/ was corrected in eight native speaker of South American varieties of Spanish. The tested subjects were recorded before and after ten sessions of speech correction. Acoustic analysis in Praat showed statistically significant higher F2 in /ʎ/ in second recording and as well as significant difference in duration. Application of this sort of work can be seen in foreign language acquisition but also in research of speech-hearing pathology. Keywords : Verbotonal theory, speech correction, system of errors, palatal lateral approximant /ʎ/, acoustic analysis